2021
DOI: 10.3390/ijerph182010910
|View full text |Cite
|
Sign up to set email alerts
|

Moving Forward: Understanding Correlates of Physical Activity and Sedentary Behaviour during COVID-19—An Integrative Review and Socioecological Approach

Abstract: Population-level physical activity (PA) and sedentary time/behaviour estimates represent a significant public health issue exacerbated by restrictions enforced to control COVID-19. This integrative review interrogated available literature to explore the pandemic’s impact on correlates of such behaviours in adults (≥18 years). Five electronic databases were systematically searched in January 2021. Data extracted from 64 articles were assessed for risk-of-bias using the Mixed Methods Assessment Tool, with correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 90 publications
(376 reference statements)
3
30
2
Order By: Relevance
“…In accord with our findings in adults and older adults [14], clear associations were identified between components of mental health and PA both in children [35] and adolescents [21,28,35]. The relationship between mental health and PA is bi-directional, where poor mental health can be both a consequence or a cause of being less physically active [47]; poor mental health was reported as an important factor contributing to lower PA during lockdown [48].…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…In accord with our findings in adults and older adults [14], clear associations were identified between components of mental health and PA both in children [35] and adolescents [21,28,35]. The relationship between mental health and PA is bi-directional, where poor mental health can be both a consequence or a cause of being less physically active [47]; poor mental health was reported as an important factor contributing to lower PA during lockdown [48].…”
Section: Discussionsupporting
confidence: 86%
“…It is clear that removing the physical opportunity to be active during the initial period of pandemic control restrictions, in line with the findings observed in adults and older adults [14], also had detrimental consequences for children and adolescents. It is perhaps pertinent to note the potential difference between the relative duration of the pandemicrelated restrictions and the long-term ramifications on PA and sedentary time/behaviour.…”
Section: The Com-b: Behavioural Targets and Policy Recommendationssupporting
confidence: 68%
See 2 more Smart Citations
“…These findings are consistent with a survey study on determinants of PA during the COVID-19 pandemic, which found that physical opportunity and reflective motivation were the most consistent predictors of behaviour (Spence et al, 2021). Knight et al (2021) also found that many themes related to physical opportunity. However, they also found that several themes mapped onto physical or psychological capability.…”
Section: Discussionmentioning
confidence: 92%